Hydrophobic / hydrophilic composite membrane for photo-thermal membrane distillation and preparation method

Preparation of sparse/hydrophilic composite membranes by electrospinning, combining the thermal pressing forming of nano CuS and PLA films, solves the problems of low photothermal conversion efficiency and thermal energy utilization in photothermal film distillation technology, and achieves efficient water separation and High-performance NaCl interception effect.

CN119158418APending Publication Date: 2024-12-20HOHAI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411604872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing photothermal conversion efficiency and thermal energy utilization rate of the photothermal film distillation technology are relatively low, and further improvement is needed to improve solar energy utilization and water separation efficiency.

Method used

Electrospinning method is used to prepare a sparse/hydrophilic composite membrane. By spinning a PVDF-DMF-acetone solution of molecular dispersed nanocuS, a nanofiber membrane is formed and heat-pressed with a hydrophilic PLA film with large pores. Reduce the total hydrogen bonding level and gas transmission resistance in the liquid-gas phase transition stage, and improve evaporation and condensation efficiency.

Benefits of technology

The efficient conversion of solar energy into distillation driving force is achieved, the photothermal conversion efficiency and steam transmission speed are improved, the photothermal conversion efficiency of 80-95% and the NaCl intercept rate of more than 99%, and the water production flux reaches 3.5±0.23LMH. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158418A_ABST
    Figure CN119158418A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrophobic / hydrophilic composite membrane for photo-thermal membrane distillation, which comprises the following steps of: 1, dissolving 10 weight percent of PVDF-HFP (Polyvinylidene Fluoride-Hexafluoropropylene) polymer particles in a mixed solvent of DMF (Dimethyl Formamide) and acetone at room temperature, and continuously stirring for 12 hours; the preparation method comprises the following steps: adding a small amount of LiCl into a solution, then filling the prepared solution into an injector with a stainless steel needle for electrospinning, dissolving a CuS monomer, ultrasonically dispersing the CuS monomer in a DMF-acetone solution for 2 hours, after electrostatic spinning, hanging a nanofiber membrane in a closed acrylic acid box, and putting 0.3 mL of original spinning solution into a culture dish for evaporation; then putting the closed box into an oven at 60 DEG C for 15 minutes; and 2, immersing the PLA membrane into a Tris-HCl buffer solution, adding 20mg of dopamine into the solution, and slightly stirring at room temperature for 24 hours to promote the formation of a PDA coating on the PLA membrane. And then, properly drying the PLA film in a drying oven at 60 DEG C for 20 minutes. And carrying out hot pressing on the treated PLA film at 50 DEG C and 0.3 MPa by using a PVDF-HFP nanofiber layer for 1 hour to obtain the final composite structure film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrophobic / hydrophilic composite membrane for photothermal membrane distillation and a preparation method thereof, belonging to the technical field of membrane distillation system application. Background Art

[0002] Membrane distillation technology is a high-efficiency process for separating the components of a mixture. This technology uses a hydrophobic semipermeable membrane to separate the mixture into two phases, thereby achieving the separation of the components. Solar-driven water-solute separation technology has the advantages of being environmentally friendly, low-cost and low-energy, and has great potential. This type of technology mainly includes traditional interfacial evaporation technology and solar membrane distillation technology that has just emerged in recent years. It has significant advantages in the fields of energy recovery and sustainable recycling of water. It also has advantages in fields including chemical industry, environmental protection, food and beverage, medicine and biotechnology. It has significant technical advantages in processes such as seawater desalination, solvent recovery, wastewater treatment, and distillation purification. Water vapor is separated from liquid water containing impurities by using temperature difference and vapor pressure difference. Commonly used membrane materials include hydrophobic polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polypropylene (PP). These membrane materials have good chemical stability and mechanical strength and can be used for a long time under high temperature and harsh environment.

[0003] In recent years, the interfacial evaporation design has made a series of progress in the rate of photothermal steam generation, but the condensation collection efficiency of water vapor is generally low. In comparison, the photothermal membrane distillation technology has better water vapor collection capacity, can operate continuously, and has good stability. The photothermal membrane distillation material is mainly composed of a hydrophobic microfiltration substrate and a surface photothermal material. The photothermal material side of the photothermal membrane contacts the feed solution, and the bottom is connected to the filtrate. Under the irradiation of sunlight, the in-situ photothermal effect is realized to convert and heat the feed solution, forming a transmembrane temperature difference and water vapor pressure difference on both sides of the membrane. According to the operation process of photothermal membrane distillation, it can be seen that the reasonable design of the photothermal membrane can optimize and improve the utilization rate of solar energy. Use photothermal materials to efficiently convert solar energy into thermal energy. Common photothermal materials include black carbon nanotubes, metal nanoparticles and polymer composites. These materials have high absorbance and low thermal emissivity, which can maximize the capture of solar energy and reduce heat energy loss. In the photothermal membrane distillation system, the heat energy converted by photothermal causes water molecules to evaporate, and the steam passes through the membrane and condenses on the other side to form pure water. This process can effectively remove dissolved salts, heavy metals, organic pollutants and microorganisms from water.

[0004] Reasonable design of photothermal membrane structure can not only improve the utilization rate of solar energy, but also improve the temperature polarization and pollution of the membrane. For example, some people modified carbon black particles with perfluorotriethoxysilane and used the immersion method to achieve self-assembly modification of PVDF microfiltration membrane to obtain a photothermal membrane with low surface energy; some people sprayed titanium nitride nanoparticles and polyvinyl alcohol solution on the surface of PVDF membrane, and the stability and anti-infiltration of the photothermal membrane were improved. In recent years, there is also a method of designing a membrane with two-sided anisotropy that has received attention, that is, the preparation of asymmetric wettability of hydrophilic / hydrophobic Janus composite membranes. In the field of photothermal membranes, the general method is to place the photothermal response material in the hydrophilic layer, and the hydrophilic layer is in direct contact with the feed solution to form a hydration layer, which is heated by the photothermal material. Although photothermal membrane distillation uses solar energy, its energy conversion efficiency is limited by material and system design, and it is necessary to further improve the photothermal conversion efficiency and thermal energy utilization. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the present invention provides a method for preparing a hydrophobic / hydrophilic composite membrane for photothermal membrane distillation and a composite membrane, wherein the composite membrane can efficiently utilize solar energy to convert into the driving force for membrane distillation, and electrospinning a PVDF-DMF-acetone solution of molecularly dispersed nano-CuS allows the surface of the nanofibers in the membrane distillation to simultaneously achieve the heating and phase change of the feed liquid at a consistent interface, thereby reducing the total level of hydrogen bonds that need to be overcome in the liquid-gas phase change stage of the membrane distillation process, and promoting the evaporation of the liquid in the photothermal membrane distillation process; by hot-pressing the above-mentioned nanofibers with a hydrophilic PLA film having large pores, the resistance to gas transmission in the membrane pore channel during the membrane distillation process is reduced, and the hydrophilic material allows the condensed water to penetrate deeper into the membrane pores and has stronger surface turbulence characteristics, thereby promoting the condensation of steam on the cold side.

[0006] Technical solution: To solve the above technical problems, the method for preparing the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation of the present invention comprises the following steps: (1) 10 wt.% PVDF-HFP polymer particles were dissolved in a mixed solvent of DMF and acetone at room temperature, and LiCl was added to the solution, with 0.005 g LiCl per g PVDF-HFP. CuS monomer was dissolved and ultrasonically dispersed in the PVDF-DMF-acetone solution for 2 h, and different amounts of CuS (0.1-0.3 g) were added to finally obtain nanofibers with different degrees of light response, and then the above solution was continuously stirred for 12 h; (2) The prepared solution was then loaded into a syringe equipped with a stainless steel needle with an inner diameter of 0.51 mm for electrospinning. The push plate rate was maintained at 8 mm / h, 11 cm away from the outermost edge of the cylindrical collector, the collector was charged with a positive voltage of 20 kV, and a negative voltage of −2 kV was applied to the steel needle. (3) After electrospinning, the nanofiber membrane was suspended in a sealed acrylic box, 0.3 mL of the original spinning solution was placed in a petri dish for evaporation, and then the sealed box was placed in an oven at 60 °C for 15 min to weld the nanofibers. The volatile organic solvent atmosphere caused the fiber to shrink and increase the fiber toughness. (4) To ensure the cohesive integrity of the final polymer film, the polylactic acid (PLA) film was immersed in a Tris-HCl buffer solution (10 mM, pH 8.5, 50 mL), and then 20 mg of dopamine was added to the solution and stirred at low speed at room temperature for 24 h to promote the formation of a PDA coating on the PLA film. The PLA film was moderately dried in an oven at 60 °C for 20 min, and then the PLA film treated with a PVDF-HFP nanofiber layer was hot-pressed at 50 °C and 0.3 MPa for 1 h.

[0007] A hydrophobic / hydrophilic composite membrane for photothermal membrane distillation comprises a hot side and a cold side, the hot side and the cold side are bonded by polydopamine, the hot side pore size is 0.1-0.2 μm, and the cold side pore size is 200-400 μm; (2) the static water contact angle of the hot side is 145° to 155°, and the static water contact angle of the cold side is 80° to 90°; the thickness of the hot side is 30-50 μm, and the thickness of the cold side is 50-100 μm. Through the following characteristics of the hot side membrane structure, the water contact angle is 145°-155°, the photothermal conversion efficiency is 80-95%, and the pore size is 0.1-0.2 μm, the nanofiber surface in the membrane distillation can synchronously realize the temperature rise and phase change of the feed liquid on a consistent interface, reducing the total level of hydrogen bonds that need to be overcome in the liquid-gas phase change stage of the membrane distillation process, thereby promoting the evaporation of the liquid in the photothermal membrane distillation process. Through the following features in the membrane pores, the hot side is 0.1-0.2μm hydrophobic pores, and the cold side pores are 200-400μm hydrophilic pores, the capillary valve effect of steam transport in membrane distillation is achieved, which promotes the transmission of steam in the membrane pores.

[0008] Beneficial effects: Compared with the prior art, the present invention has the following advantages: The hydrophobic / hydrophilic composite membrane for photothermal membrane distillation obtained by the preparation method of the present invention has a hot side pore size of 0.1-0.2 μm, a cold side pore size of 200-400 μm, a hot side static water contact angle of 145° to 155°, a cold side static water contact angle of 80° to 90°, a hot side thickness of 30-50 μm, a cold side thickness of 50-100 μm, an overall thermal conductivity of the membrane of 0.8-1.0 Wm-2k-1, and a surface thermal conductivity of 5-20 Wm-2k-1, the photothermal conversion efficiency on the hot side of the membrane is 80-95%, and the visible light absorbance is not less than 0.7. Overall, such a membrane structure is used in photothermal membrane distillation, so that the nanofiber surface in the membrane distillation can simultaneously realize the heating and phase change of the feed liquid on a consistent interface, reducing the total level of hydrogen bonds that need to be overcome in the liquid-gas phase change stage of the membrane distillation process. The efficiency of evaporation of the feed liquid from liquid to gas is high, the gas transmission speed in the membrane pores is fast, and the gas condensation and transportation transmission speed is fast. Therefore, under the conditions of 3.5%wt mass fraction NaCl feed liquid, a flux of 3.5±0.23LMH is achieved, and the NaCl retention rate is maintained above 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 Schematic diagram of the water production flux diagram.

[0010] Figure 2 Schematic diagram of the produced water conductivity diagram.

[0011] Figure 3 This is the Fourier infrared spectrum.

[0012] Figure 4 This is a scanning electron microscope image of the cross section.

[0013] Figure 5 This is a scanning electron microscope image of the surface. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the accompanying drawings.

[0015] A method for preparing a hydrophobic / hydrophilic composite membrane for photothermal membrane distillation comprises the following steps: (1) Dissolving PVDF-HFP polymer particles in a mixed solvent of DMF and acetone at room temperature, wherein the mass fraction of PVDF-HFP in the mixed solution is 8-15 wt.%, DMF is 65-75%, and acetone is 15-22%, and then adding LiCl to the mixed solution, wherein each gram of PVDF-HFP mixed solution contains 0.005-0.01 g of LiCl, dissolving and ultrasonically dispersing the material having transition metal sulfide semiconductor properties in the PVDF-DMF-acetone solution for 2-3 hours, and then continuously stirring the above solution for 8-16 hours; (2) The prepared solution was then loaded into a syringe equipped with a stainless steel needle with an inner diameter of 0.51 mm for electrospinning. The push plate rate was maintained at 8-12 mm / h, 8-12 cm away from the outermost edge of the cylindrical collector, the collector was charged with a positive voltage of 18-22 kV, and a negative voltage of -4 to -2 kV was applied to the steel needle; (3) After electrospinning, the nanofiber membrane was suspended in a sealed acrylic box, 0.3-1.0 mL of the original spinning solution was placed in a petri dish for evaporation, and then the sealed box was placed in an oven at 58-62 °C for 14-16 minutes to weld the nanofibers. The volatile organic solvent atmosphere caused the fiber to shrink and increase the fiber toughness, forming a PVDF-HFP nanofiber layer. (4) Immerse the polylactic acid film PLA in a Tris-HCl buffer solution with a molar concentration of 10-11 mM and a pH of 8.5-9, then add dopamine to the solution at a rate of 0.01 m 2 The PLA film is treated with 10-20 mg dopamine solution, the mass fraction of the dopamine solution is 0.2-0.4 mg / mL, and stirred at a speed of 300-400 rpm for 23-25 ​​hours at room temperature, and the PLA film is dried in an oven at 60°C for 15-25 minutes, and then the PLA film is hot-pressed with a PVDF-HFP nanofiber layer at a temperature of 45-55°C and a pressure of 0.3-0.4MPa for 0.95-1.05 h. The prepared hydrophobic / hydrophilic composite membrane for photothermal membrane distillation comprises a hot side and a cold side, the hot side and the cold side are bonded by polydopamine, the hot side pore size is 0.1-0.2 μm, and the cold side pore size is 200-400 μm; the static water contact angle of the hot side is 145° to 155°, and the static water contact angle of the cold side is 80° to 90°; the hot side thickness is 30-50 μm, and the cold side thickness is 50-100 μm.

[0016] In the present invention, in step (1), the material having transition metal sulfide semiconductor properties is one of molybdenum disulfide, copper selenide, tungsten oxide, lead sulfide or copper sulfide.

[0017] Example 1 Preparation of the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation of the present invention PVDF-HFP polymer particles were dissolved in a mixed solvent of DMF and acetone at room temperature, wherein the mass fraction of PVDF-HFP was 9 wt.%, the mass fraction of DMF was 72 wt.%, and the mass fraction of acetone was 19 wt.%. After the configuration was completed, a small amount of LiCl was added to the solution, wherein the mass fraction of LiCl was 0.01 wt.%. Lithium ions have the characteristic of occupying hydrogen bonding sites in a polymer long chain solution, which can not only improve the electrospinning property of the solution, but also increase the viscosity of the solution. Dissolve the CuS nanomonomer and ultrasonically disperse it in the solution for 2 hours, wherein the amount of CuS added is 20% of the mass of the added PVDF-HFP, so as to finally obtain nanofibers with different light response degrees, and then stir the solution continuously for 12 hours; The prepared solution was loaded into a syringe equipped with a stainless steel needle (inner diameter 0.51 mm) for electrospinning. A high-pressure, short-distance spinning method was used. The push plate rate was maintained at 8 mm / h, 11 cm away from the outermost edge of the cylindrical collector. The collector was charged with a positive voltage of 20 kV, and a negative voltage of −2 kV was applied to the steel needle. The spinning temperature was 20 °C and the humidity was 70%. After electrospinning, the spun fiber layer was welded by fumigation. The nanofiber membrane was suspended in a sealed acrylic box, and the original spinning solution was placed in a petri dish for evaporation. The amount of the evaporated solution was 66.7 mL of the original spinning solution per square meter of the sealed box. The sealed box was then placed in an oven at 60°C for 15 minutes to weld the nanofibers. The volatile organic solvent atmosphere caused the fiber to shrink and increase the fiber toughness. To ensure the cohesive integrity of the final polymer film, the polylactic acid (PLA) film was immersed in Tris-HCl buffer solution, (10 mM, pH 8.5), and then dopamine (0.4 g / L) was added to the solution, followed by low-speed stirring at room temperature for 24 h to promote the formation of PDA coating on the PLA film, and subsequently, the PLA film was moderately dried in an oven at 70 °C for 15 min; The photoresponsive nanofibers of the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation prepared in step 1 and the PLA membrane subjected to heat pressing treatment at 50° C. and 0.3 MPa for 1 h in this step are used to obtain the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation of the present invention; The membrane was placed in a direct contact membrane distillation membrane pool, with 3.5 wt % NaCl solution as the membrane distillation feed liquid, the hot side feed liquid temperature was 20 °C, the cold side circulating water temperature was 20 °C, the flow rate on both sides was 0.36 mL / s, and the membrane surface was vertically exposed to the 1sun standard solar intensity of AM1.5. A continuous 24 h membrane distillation test of water production was carried out. The water flux results of the test are shown in the attached Figure 1 As shown in the M2 curve, the water flux is in the range of 2.6-2.2LMH. The test results of water conductivity are shown in the attached Figure 2 As shown in the M2 curve, the NaCl retention rate is higher than 99%.

[0018] The Fourier transform infrared spectrum of the photothermal surface of the film is shown in the attached figure. Figure 3 The cross-section and surface scanning electron microscopy images of the membrane are shown in the attached Figure 4 and Figure 5 shown.

[0019] Example 2 Preparation of MoS2 Photothermal Layer for Photothermal Membrane Distillation Hydrophobic / Hydrophilic Composite Membrane Dissolve PVDF-HFP polymer particles in a mixed solvent of DMF and acetone at room temperature, wherein the mass fraction of PVDF-HFP is 10 wt.%, the mass fraction of DMF is 70 wt.%, and the mass fraction of acetone is 20 wt.%. After the configuration is completed, add a small amount of LiCl to the solution, wherein the mass fraction of LiCl is 0.01 wt.%, which can improve the electrospinning property of the solution and increase the viscosity of the solution; Dissolving molybdenum disulfide and ultrasonically dispersing it in the above solution for 2 hours, wherein the amount of molybdenum disulfide added is 10% of the mass of the added PVDF-HFP, so as to finally obtain nanofibers with different degrees of light response, and then continuously stirring the above solution for 12 hours; The prepared solution was loaded into a syringe equipped with a stainless steel needle (inner diameter 0.51 mm) for electrospinning. A high-pressure, short-distance spinning method was used. The push plate rate was maintained at 8 mm / h, 11 cm away from the outermost edge of the cylindrical collector. The collector was charged with a positive voltage of 20 kV, and a negative voltage of −2 kV was applied to the steel needle. The spinning temperature was 20 °C and the humidity was 80%. After electrospinning, the spun fiber layer was welded by fumigation. The nanofiber membrane was suspended in a sealed acrylic box, and the original spinning solution was placed in a petri dish for evaporation. The amount of the evaporated solution was 66.7 mL of the original spinning solution per square meter of the sealed box. The sealed box was then placed in an oven at 60°C for 15 minutes to weld the nanofibers. The volatile organic solvent atmosphere caused the fiber to shrink and increase the fiber toughness. To ensure the cohesive integrity of the final polymer film, the polylactic acid (PLA) film was immersed in Tris-HCl buffer solution, (10 mM, pH 8.5), and then dopamine (0.4 g / L) was added to the solution, followed by low-speed stirring at room temperature for 24 h to promote the formation of PDA coating on the PLA film, and subsequently, the PLA film was moderately dried in an oven at 60 °C for 15 min; The prepared photoresponsive nanofibers of the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation and the PLA membrane of this step were hot-pressed at 50° C. and 0.3 MPa for 1 h to obtain the hydrophobic / hydrophilic composite membrane for photothermal membrane distillation of the molybdenum disulfide photothermal layer of this embodiment.

[0020] Dissolve PVDF-HFP polymer particles in a mixed solvent of DMF and acetone at room temperature, wherein the mass fraction of PVDF-HFP is 10 wt.%, the mass fraction of DMF is 70 wt.%, and the mass fraction of acetone is 20 wt.%. After the configuration is completed, add a small amount of LiCl to the solution, wherein the mass fraction of LiCl is about 0.01 wt.%. Lithium ions have the characteristic of occupying hydrogen bonding sites in a polymer long chain solution, which can not only improve the electrospinning property of the solution, but also increase the viscosity of the solution. Then stir the above solution continuously for 12 hours; The prepared solution was loaded into a syringe equipped with a stainless steel needle (inner diameter 0.51 mm) for electrospinning. A high-pressure, short-distance spinning method was used. The push plate rate was maintained at 8 mm / h, 11 cm away from the outermost edge of the cylindrical collector. The collector was charged with a positive voltage of 20 kV, and a negative voltage of −2 kV was applied to the steel needle. The spinning temperature was 20 °C and the humidity was 70%. After electrospinning, the spun fiber layer was welded by fumigation. The nanofiber membrane was suspended in a sealed acrylic box, and the original spinning solution was placed in a petri dish for evaporation. The amount of the evaporated solution was 66.7 mL of the original spinning solution per square meter of the sealed box. The sealed box was then placed in an oven at 60°C for 15 minutes to weld the nanofibers. To ensure the cohesive integrity of the final polymer film, the polylactic acid (PLA) film was immersed in Tris-HCl buffer solution, (10 mM, pH 8.5), and then dopamine (0.4 g / L) was added to the solution, followed by low-speed stirring at room temperature for 24 h to promote the formation of PDA coating on the PLA film, and subsequently, the PLA film was moderately dried in an oven at 70 °C for 15 min; The nanofibers of the hydrophobic / hydrophilic composite membrane for membrane distillation prepared in step 1 and the PLA membrane obtained in this step were hot-pressed at 50° C. and 0.4 MPa for 1 h to obtain the hydrophobic / hydrophilic composite membrane for membrane distillation of this embodiment.

[0021] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a hydrophobic / hydrophilic composite membrane for photothermal membrane distillation, characterized in that: The following steps are involved: (1) Dissolving PVDF-HFP polymer particles in a mixed solvent of DMF and acetone at room temperature, wherein the mass fraction of PVDF-HFP in the mixed solution is 8-15 wt.%, DMF is 65-75%, and acetone is 15-22%, and then adding LiCl to the mixed solution, wherein each gram of PVDF-HFP mixed solution contains 0.005-0.01 g of LiCl, dissolving and ultrasonically dispersing the material having transition metal sulfide semiconductor properties in the PVDF-DMF-acetone solution for 2-3 hours, and then continuously stirring the above solution for 8-16 hours; (2) The prepared solution was then loaded into a syringe equipped with a stainless steel needle with an inner diameter of 0.51 mm for electrospinning. The push plate speed was maintained at 8-12 mm / h, 8-12 cm away from the outermost edge of the cylindrical collector, the collector was charged with a positive voltage of 18-22 kV, and a negative voltage of -4 to -2 kV was applied to the steel needle; (3) After electrospinning, the nanofiber membrane was suspended in a sealed acrylic box, 0.3-1.0 mL of the original spinning solution was placed in a petri dish for evaporation, and then the sealed box was placed in an oven at 58-62 °C for 14-16 minutes to weld the nanofibers. The volatile organic solvent atmosphere caused the fiber to shrink and increase the fiber toughness, forming a PVDF-HFP nanofiber layer. (4) Immerse the polylactic acid film PLA in a Tris-HCl buffer solution with a molar concentration of 10-11 mM and a pH of 8.5-9, then add dopamine to the solution at a concentration of 0.01 mM. 2 The PLA film was treated with 10-20 mg dopamine solution with a mass fraction of 0.2-0.4 mg / mL and stirred at 300-400 rpm for 23-25 ​​h at room temperature. The PLA film was dried in an oven at 60 °C for 15-25 min and then hot-pressed with a PVDF-HFP nanofiber layer at 45-55 °C and a pressure of 0.3 -0.4 MPa for 0.95-1.05 h.

2. A method for preparing a hydrophobic / hydrophilic composite membrane for photothermal membrane distillation, characterized in that: In the step (1), the material having transition metal sulfide semiconductor properties is one of molybdenum disulfide, copper selenide, tungsten oxide, lead sulfide or copper sulfide.

3. A hydrophobic / hydrophilic composite membrane for photothermal membrane distillation, characterized in that: It comprises a hot side and a cold side, the hot side and the cold side are adhered by polydopamine, the pore size of the hot side is 0.1-0.2 μm, and the pore size of the cold side is 200-400 μm; the static water contact angle of the hot side is 145° to 155°, and the static water contact angle of the cold side is 80° to 90°; the thickness of the hot side is 30-50 μm, and the thickness of the cold side is 50-100 μm.